Gestural Interaction for Accessibility of Web Videos - Funes, Marcio Maestrelo; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Recently the interest in video content sharing platforms, such Youtube and Netflix, has increased considerably attracting users with different profiles, including visually impaired. Although initiatives such as WCAG 2.0 (Web Content Acessibility Guidelines) set guidelines for video players development, there is still a need for investigation about how to improve the level of accessibility of visually impaired throughout the process of video media interaction, from browsing to the use of the player interface. The aim of this paper is to present an analysis conducted with 18 visually impaired users to access Web-video players through gestures. The analysis was carried out to check if there is improvement in the level of accessibility to access Web-video players through gestures if compared the usual access interfaces (keyboard, mouse and screen readers).